Effects of aging on calcium channels in skeletal muscle - Dong, Mingyi; Maturana, Andrés Daniel (Frontiers in Molecular Biosciences, 2025)
In skeletal muscle, calcium is not only essential to stimulate and sustain their contractions but also for muscle embryogenesis, regeneration, energy production in mitochondria, and fusion. Different ion channels contribute to achieving the various functions of calcium in skeletal muscles. Muscle contraction is initiated by releasing calcium from the sarcoplasmic reticulum through the ryanodine receptor channels gated mechanically by four dihydropyridine receptors of T-tubules. The calcium influx through store-operated calcium channels sustains the contraction and stimulates muscle regeneration. Mitochondrial calcium uniporter allows the calcium entry into mitochondria to stimulate oxidative phosphorylation. Aging alters the expression and activity of these different calcium channels, resulting in a reduction of skeletal muscle force generation and regeneration capacity. Regular physical training and bioactive molecules from nutrients can prevent the effects of aging on calcium channels. This review focuses on the current knowledge of the effects of aging on skeletal muscles’ calcium channels.